2016
DOI: 10.18632/oncotarget.12873
|View full text |Cite
|
Sign up to set email alerts
|

miR-31 affects colorectal cancer cells by inhibiting autophagy in cancer-associated fibroblasts

Abstract: Autophagy is a double-edged sword in tumor development. Recent studies have found that miRNAs have an inhibitory effect on the regulation of autophagy. It has been reported that miR-31 plays an important role in the development of colorectal cancer. However, what role miR-31 plays in colorectal cancer-associated fibroblasts (CAFs) has not been determined. In this study, we confirmed that the expression of miR-31 in CAFs was higher than in normal colorectal fibroblasts (NFs). We also found that treatment of CAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Consistent with the report above, our results in this study also discovered that miR-31 was high-expressed in CRC tissues. What's more, miR-31 is proved to be correlated to the metastasis of CRC and can regulate autophagy, proliferation, and chemoresistance of CRC cells (16,29,30). Similarly, in this study, the results con rmed that miR-31 overexpression not only promoted the migration, invasion, and suppressed the apoptosis of CRC cells but also counteracted the effect of circ_0026344.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with the report above, our results in this study also discovered that miR-31 was high-expressed in CRC tissues. What's more, miR-31 is proved to be correlated to the metastasis of CRC and can regulate autophagy, proliferation, and chemoresistance of CRC cells (16,29,30). Similarly, in this study, the results con rmed that miR-31 overexpression not only promoted the migration, invasion, and suppressed the apoptosis of CRC cells but also counteracted the effect of circ_0026344.…”
Section: Discussionsupporting
confidence: 74%
“…29 Moreover, Yang et al displayed miR-31 regulated colorectal cancer via autophagy. 30 At presently, there was wealth of researches on miR-31 in cancer. Studies had proved that miR-31 was highly expressed in colorectal cancer, lung cancer, and other cancers, but it was low in bladder cancer, gastric cancer, and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in CRC cells, LOC554202 has a tumor suppressor role in the activation of specific caspase cleavage cascades, and low expression of LOC554202 was associated with advanced pathologic stage and increased tumor size (32). miR-31 is a widely investigated miRNA and studies have reported controversial conclusions regarding its role in CRC cells (52)(53)(54)(55)(56). These studies suggest that a high expression of this miRNA in cancer does not always result in a decreased tumor growth, including that noted in cases of the oncosuppressors p53 and phosphatase and tensin homolog.…”
Section: Os ---------------------------------------------------------mentioning
confidence: 99%